Doxorubicin persistently rewires cardiac circadian homeostasis in mice - Ferreira, Luciana L (2019)
Circadian rhythms disruption can be the cause of chronic diseases. External cues, including therapeutic drugs, have been shown to modulate peripheral-circadian clocks. Since anthracycline cardiotoxicity is associated with loss of mitochondrial function and metabolic remodeling, we investigated whether the energetic failure induced by sub-chronic doxorubicin (DOX) treatment in juvenile mice was associated with persistent disruption of circadian regulators. Juvenile C57BL/6J male mice were subjected to a sub-chronic DOX treatment (4 weekly injections of 5 mg/kg DOX) and several cardiac parameters, as well as circadian-gene expression and acetylation patterns, were analyzed after 6 weeks of recovery time. Complementary experiments were performed with Mouse Embryonic Fibroblasts (MEFs) and Human Embryonic Kidney 293 cells. DOX-treated juvenile mice showed cardiotoxicity markers and persistent alterations of transcriptional- and signaling cardiac circadian homeostasis. The results showed a delayed influence of DOX on gene expression, accompanied by changes in SIRT1-mediated cyclic deacetylation. The mechanism behind DOX interference with the circadian clock was further studied in vitro, in which were observed alterations of circadian-gene expression and increased BMAL1 SIRT1-mediated deacetylation. In conclusion, DOX treatment in juvenile mice resulted in disruption of oscillatory molecular mechanisms including gene expression and acetylation profiles.